Study for microstrip patch antenna for 5g networks - Rafdzi, Muhammad Faiz; Mohamad, Sarah Yasmin; Ruslan, Ahmad Alhadi; Abdul Malek, Norun Farihah; Islam, Md. Rafiqul; Hassan Abdalla Hashim, Aisha (IEEE, 2020)
—In this paper, a microstrip patch antenna is proposed to be implemented for 5G broadband wireless communication. The single element antenna was designed to operate in the Priority 1 spectrum 3.5 GHz band set by the Malaysian Communications and Multimedia Commission (MCMC). The antenna was built on a Rogers RT5880 substrate with a dimension of 44.1 mm x 35.1 mm x 1.57 mm, which has a dielectric constant () of 2.2 and loss tangent () of 0.0009. The simulated performances of the antenna achieved a return loss of 26.347 dB at 3.5 GHz, bandwidth of 641.2 MHz ranging from 3.282 GHz to 3.910 GHz, and a gain with value of 3.68 dBi. The fabricated antenna was measured using Virtual Network Analyzer (VNA) for real world measurement, and the return loss at 3.5 GHz exhibits a value of 12.146 dB. The error was identified and simulated in CST-MWS software, and preventive measures have been listed.